Rancang Bangun Tata Kelola Kinerja Perguruan Tinggi Menggunakan IT Balanced Scorecard - Solechan, Achmad; Prasandy, Teguh (JSINBIS (Jurnal Sistem Informasi Bisnis), 2016)
Budgeting most colleges are not based on good governance and conceptual, but based on short-term needs in each college. Other problems are related to the use of information technology in both hardware, software and brain ware (user) in the management of information technology is still not well-thought in its development. This research aims to design a wake-up governance by using the Information Technology IT Balanced Scorecard framework is a system of management, measurement and control quickly, accurately and comprehensively can provide insight to the Leadership of the portrait and the development of information technology in institution. Information system development using SDLC (system development life cycle). College performance measurement method using IT balanced scorecard framework. The results showed that the use of information systems governance college performance using IT Balanced Scorecard help the efficiency and effectiveness in making an evaluation report IT governance, helping the presentation of information and error reduction calculations, the transaction data maintained intact his security, was able to complete the reporting process with fast, speed up the calculation process and the conclusion of the assessment of the performance of the college.Â